A Systems Perspective on Business Model Evolution: The Case of an Agricultural Information Service Provider in India. Issue 5 (October 2017) - Velu, Chander
Abstract : This paper explores how the organizational capabilities of a firm enable business model evolution by examining the development of a new firm that provides mobile-phone-based information services for farmers in India. We argue that these organizational capabilities are part of the dynamic capabilities of the firm. We use a longitudinal and in-depth single case study to extend our understanding of the mechanism for business model evolution in new firms. The study shows three themes emerging from the data analysis of the case study by drawing on the literatures on systems thinking, dynamic capabilities and business model evolution. The three themes are balanced redundancy, requisite variety and cognitive discretion, which enable a firm to achieve congruence between the components of the business model in order to deliver the customer value proposition. We explain how these three micro-foundations of dynamic capabilities enable a firm to evolve its business model. We contribute to the business model and dynamic capabilities literature by proposing a systems perspective on business models and their evolution. Highlights: We study a mobile-phone-based information services firm for farmers in India. Explores how organizational capabilities enabled business model evolution. Draws on systems thinking, dynamic capabilities and business model literatures. Develops balanced redundancy, requisite variety and cognitive discretion as themes. These themes on organizational capabilities enabled business model evolution.